Challenger the final voyage - Lewis, Richard S. 1916- (Columbia Univ. Pr., 1988)
Includes bibliographical references and index. An account of the space shuttle accident that took the lives of seven people. Also considers the physical and managerial causes of the accident.
Keywords: Challenger (Spacecraft) -- Accidents; Geschichte 1986; Raumfahrtunfall; Challenger -- Raumtransporter